Early childhood policies and systems in eight countries : findings from IEA's early childhood education study - Bertram, Tony; Pascal, Chris (Springer Open, 2016)
This report provides an overview of policy strategies on early childhood education settings (from birth to primary schooling) in eight countries. Data were collected using a policy questionnaire addressed to and completed by the National Research Coordinator(s) (NRC) of Chile, the Czech Republic, Denmark, Estonia, Italy, Poland, the Russian Federation and the United States. The countries that participated provide interesting illustrations of early childhood education policy in action in a range of diverse contexts.